PkM Introduction of Carbon Trading as an Alternative for Climate Change Mitigation in the Millennial Generation - Darwin Hartono; Tampubolon, Endy Grade; Anco (Jurnal Pengabdian Pancasila (JPP), 2024)
One of these risks is climate change. A perception survey from the World Economic Forum Global Risk Report (2022) states that climate change in the next 10 years is considered the risk that poses the greatest long-term threat. Without joint mitigation efforts to reduce Green House Gas (GHG) emissions, the Paris Agreement goal of limiting global warming from 1.5 degrees C to 2.0 degrees C will be out of reach. Both the government and the private sector need to take the climate emergency seriously by increasing their ambition to achieve net-zero emissions by the middle of this century. Carbon trading or commonly called carbon trading is a concept that emerged through the Kyoto Protocol in 1997. A year when many countries were worried about world environmental conditions (Pinkse & Kolk, 2007). Up to 180 countries signed the agreement to reduce the impact of each country's greenhouse gas emissions from 2008 to 2012 to 5 percent below the amount of gas emissions in 1999, which in reality could not be achieved. Despite the uncertainty surrounding what kind of international framework might be effective in replacing the Kyoto Protocol or the criticisms that have emerged against carbon trading, carbon markets remain a central component of global climate policy. The method of implementing service activities is that partners are provided with counseling about climate change that is occurring and carbon trading efforts as alternative climate change mitigation, discussions and questions and answers regarding climate change and carbon trading.